Particulate Matter Exposure and Preterm Birth: Estimates of U.S. Attributable Burden and Economic Costs - Trasande, Leonardo; Malecha, Patrick; Attina, Teresa M. (Environmental health perspectives, 2016)
Preterm birth (PTB) rates (11.4% in 2013) in the United States remain high and are a substantial cause of morbidity. Studies of prenatal exposure have associated particulate matter ≤ 2.5 μm in diameter (PM2.5) and other ambient air pollutants with adverse birth outcomes; yet, to our knowledge, burden and costs of PM2.5-attributable PTB have not been estimated in the United States. We aimed to estimate burden of PTB in the United States and economic costs attributable to PM2.5 exposure in 2010. Annual deciles of PM2.5 were obtained from the U.S. Environmental Protection Agency. We converted PTB odds ratio (OR), identified in a previous meta-analysis (1.15 per 10 μg/m3 for our base case, 1.07-1.16 for low- and high-end scenarios) to relative risk (RRs), to obtain an estimate that better represents the true relative risk. A reference level (RL) of 8.8 μg/m3 was applied. We then used the RR estimates and county-level PTB prevalence to quantify PM2.5-attributable PTB. Direct medical costs were obtained from the 2007 Institute of Medicine report, and lost economic productivity (LEP) was estimated using a meta-analysis of PTB-associated IQ loss, and well-established relationships of IQ loss with LEP. All costs were calculated using 2010 dollars. An estimated 3.32% of PTBs nationally (corresponding to 15,808 PTBs) in 2010 could be attributed to PM2.5 (PM2.5 > 8.8 μg/m3). Attributable PTBs cost were estimated at $5.09 billion [sensitivity analysis (SA): $2.43-9.66 B], of which $760 million were spent for medical care (SA: $362 M-1.44 B). The estimated PM2.5 attributable fraction (AF) of PTB was highest in urban counties, with highest AFs in the Ohio Valley and the southern United States. PM2.5 may contribute substantially to burden and costs of PTB in the United States, and considerable health and economic benefits could be achieved through environmental regulatory interventions that reduce PM2.5 exposure in pregnancy. Citation: Trasande L, Malecha P, Attina TM. 2016. Particulate matter exposure and preterm birth: estimates of U.S. attributable burden and economic costs. Environ Health Perspect 124:1913-1918; http://dx.doi.org/10.1289/ehp.1510810.